The creation of the American Republic, 1776-1787 - Wood, Gordon S. (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia., 1998)
This text describes the evolution of political thought from the Declaration of Independence to the ratification of the Constitution. The author discusses the debate over Republicanism.